2001
DOI: 10.1142/s0218810401000540
|View full text |Cite
|
Sign up to set email alerts
|

Current Treatment of Ganglion of the Wrist

Abstract: Ganglion of the wrist is one of the the most common lesions of the hand. The cause of pain in an occult dorsal wrist ganglion has been linked to compression of the posterior interosseous nerve at the wrist. A case is presented in this paper and the pathoanatomy discussed. Ultrasound-guided aspiration after hyaluronidase instillation provided a useful alternative to surgery with a high success rate. Arthroscopic decompression for dorsal and palmar wrist ganglia offered the patient the benefit of smaller surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 29 publications
1
32
1
6
Order By: Relevance
“…Previously, there had been no consensus as to whether entering the midcarpal joint is necessary when arthroscopically resecting ganglion cysts. Ho et al 40 reported 2 recurrences after resection of ganglion cysts originating from the midcarpal joint, and ultimately concluded that arthroscopic resection was not indicated for cysts originating from this area. Another series reported success with arthroscopic resection of dorsal midcarpal ganglion cysts, but their cohort was small.…”
Section: 24mentioning
confidence: 99%
“…Previously, there had been no consensus as to whether entering the midcarpal joint is necessary when arthroscopically resecting ganglion cysts. Ho et al 40 reported 2 recurrences after resection of ganglion cysts originating from the midcarpal joint, and ultimately concluded that arthroscopic resection was not indicated for cysts originating from this area. Another series reported success with arthroscopic resection of dorsal midcarpal ganglion cysts, but their cohort was small.…”
Section: 24mentioning
confidence: 99%
“…Other studies have reported the incidence of stalks to range from 9% to 30% [7,10,19]. In our study, discrete stalks were identified in only nine of 41 (22%) patients.…”
Section: Discussioncontrasting
confidence: 55%
“…Accordingly, arthroscopic resection has been proposed as a potentially more favorable alternative to open resection, with recurrence rates of 0% to 11% [11,12,15,16] and improved pain, grip strength, and wrist motion [1,2,[7][8][9][10]. Further, arthroscopic resection reportedly is associated with no scaphoid subluxation or chronic scapholunate instability attributable to ligament injury during surgery that has been reported after open resection [2,3,8,11,12,16], and an improved cosmetic appearance [11].…”
Section: Introductionmentioning
confidence: 99%
“…Ho et al 16 concluded that sclerotherapy may be an alternative to surgery in the treatment of ganglions. Linetsky 17 described that sclerotherapy may be applicable to treat many symptomatic cysts of the musculoskeletal system.…”
Section: Discussionmentioning
confidence: 99%